2020
DOI: 10.1111/ajt.15700
|View full text |Cite
|
Sign up to set email alerts
|

Applicability, safety, and biological activity of regulatory T cell therapy in liver transplantation

Abstract: Regulatory T cells (Tregs) are a lymphocyte subset with intrinsic immunosuppressive properties that can be expanded in large numbers ex vivo and have been shown to prevent allograft rejection and promote tolerance in animal models. To investigate the safety, applicability, and biological activity of autologous Treg adoptive transfer in humans, we conducted an open‐label, dose‐escalation, Phase I clinical trial in liver transplantation. Patients were enrolled while awaiting liver transplantation or 6‐12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(183 citation statements)
references
References 35 publications
1
182
0
Order By: Relevance
“…A total of nine patients (three patients less than 6 months after transplantation and six patients more than 6 months post-transplantation) received the GMP-Treg cells. The study showed that Treg cell therapy was safe and increased the pool of circulating Treg cells (98).…”
Section: Polyclonal Regulatory T Cells and Low Dose Il-2 Therapy In Lmentioning
confidence: 98%
“…A total of nine patients (three patients less than 6 months after transplantation and six patients more than 6 months post-transplantation) received the GMP-Treg cells. The study showed that Treg cell therapy was safe and increased the pool of circulating Treg cells (98).…”
Section: Polyclonal Regulatory T Cells and Low Dose Il-2 Therapy In Lmentioning
confidence: 98%
“…Adoptive T Reg transfer was protective in mice, and currently several clinical trials are testing the efficiency and safety in humans ( Romano et al, 2017 ). Another study tested the T Reg therapy in patients 6–12 months after liver transplantation and demonstrated an increase in circulating T Reg cells and reduced anti-donor T cell response ( Sanchez-Fueyo et al, 2020 ). Although the long-term effects are not evaluated, T Reg therapy could be a promising therapeutic approach.…”
Section: The T H 17/t Reg Cellmentioning
confidence: 99%
“…Mammalian transporter of rapamycin inhibition via rapamycin is a part of current immunosuppression protocols as well as ex vivo GMP Treg cell expansion protocols (1,19,20,111). This is because rapamycin improves Treg cell expansion, FOXP3 expression, and immunosuppressive function (25).…”
Section: Mtormentioning
confidence: 99%
“…In this review, we discuss Treg cell metabolism and interlink it with their diverse functions. From a clinical perspective, the initial data from Phase I trials in transplant and non-transplant settings has shown Treg cells to be safe (1,(19)(20)(21)(22). The current Good Manufacturing Practice (GMP) protocols center on the hypothesis that the infusion of expanded autologous Treg cells could modulate the inflamed allograft microenvironment in favor of immunoregulation instead.…”
Section: Introductionmentioning
confidence: 99%